2002
DOI: 10.1007/s00468-002-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of mangrove ecosystems in developing countries

Abstract: There is limited information available on the status of and threats to mangroves in developing countries in the Asia-Pacific region. In the recent years, there has been a significant increase in scientific and volunteer surveys. However, this information is usually not well integrated with information on human activities that have the potential to contribute to the degradation of these ecosystems. A project "Coastal Habitats at Risk" is being developed jointly by the United Nations University (UNU) and the Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 1 publication
1
35
0
Order By: Relevance
“…Here we assume that displacement takes the form of a 100-km-wide delta function in which half of the zone is lifted and half is depressed. The magnitude is similar to that estimated for the recent Sumatra tsunami, with instantaneous, initial upward and downward displacements of +7.2 m and -3.5 m, respectively (Yalciner et al, 2004 (Adeel & Pomeroy, 2002) A coral reef can affect wave propagation and development by presenting an abrupt change in bathymetry and through increased bottom roughness. To model the former effect, at any grid point where a reef is present, the bottom depth is replaced by a step that rises to 1 m below the surface.…”
Section: Model Description and Setupsupporting
confidence: 76%
“…Here we assume that displacement takes the form of a 100-km-wide delta function in which half of the zone is lifted and half is depressed. The magnitude is similar to that estimated for the recent Sumatra tsunami, with instantaneous, initial upward and downward displacements of +7.2 m and -3.5 m, respectively (Yalciner et al, 2004 (Adeel & Pomeroy, 2002) A coral reef can affect wave propagation and development by presenting an abrupt change in bathymetry and through increased bottom roughness. To model the former effect, at any grid point where a reef is present, the bottom depth is replaced by a step that rises to 1 m below the surface.…”
Section: Model Description and Setupsupporting
confidence: 76%
“…Assuming that the rate of change in mangrove area was constant between years, the rates of loss during 1997-2002 were high, up to 20% per year in zones 1 and 3, although actual rates for 1998-1999 when the construction took place would no doubt be much higher. Ramírez-Garcia et al (1998) concluded the rate of loss seen in Mexico of 1.4% annually was high and Adeel and Pomeroy (2002) notes that declines of 2-8% per year were fast. Dahdouh-Guebas and Koedam (2002) explain that it is possible to incorporate previous maps of past mangrove extent with current field data on vegetation structure to gain insight into current and future mangrove dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove forests have the highest productivity among coastal wetlands after coral reefs. Around 90% of all marine organisms spend some portion of their life cycle within the mangrove ecosystem (Adeel and Pomeroy, 2002). Mangrove ecosystem commands the highest importance because of its biological productivity and specialized diversity.…”
Section: Introductionmentioning
confidence: 99%